Fruit yield and gas exchange of Tahiti lime at different irrigation depths in the Amazon - Pinto, João V. de N.; Costa, Deborah L. P.; Costa, Ana P. da S.; Pires, Mateus P.; Rolim, Glauco de S. [UNESP]; de Sousa, Adriano M. L.; Ortega-Farias, Samuel; de Souza, Paulo J. de O. P. (FapUNIFESP (SciELO), 2023)
Tahiti lime is a species of great economic importance worldwide. In Brazil, production is concentrated in the states of São Paulo and Pará, where it is usually grafted onto the Rangpur lime. This study aimed to analyze the effects of different irrigation depths on the fruit yield, phenology, and gas exchange of Tahiti lime trees grafted onto Swingle citrumelo. Irrigation was performed during the first year at four different irrigation depths in a random block design with five blocks and four treatments to maintain the soil matric potential in the following ranges: T1: below-50 kPa, T2: from-30 to-50 kPa, T3: from-10 to-30 kPa, and T4: above-10 kPa. The flowering, carbon assimilation rate (A), stomatal conductance (gs), transpiration (E), and fruit yield were measured. Fruits were harvested earlier in the most irrigated treatment, T4, and the yield increased from 2.22 to 6.89 kg per plant from T1 to T4. The average fruit weight escalated from 78.6 to 96.1 g from T1 to T4, and carbon assimilation increased from 6.89 to 9.51 μmol CO2 m-2 s-1 from T1 to T4.
Produtividade e trocas gasosas do limão Tahiti em diferentes lâminas de irrigação na Amazônia
Keywords: citriculture; sustainability; water management; water resources